Marginal and Internal Adaptation of Different Superstructure and Abutment Materials Using Two Different Implant Systems for Five-Unit Implant-Supported Fixed Partial Dentures: An In Vitro Study - KAHRAMANOĞLU, ERKUT; ÖZKAN, YASEMİN (QUINTESSENCE PUBLISHING CO INC, 2013)
Purpose: To evaluate the marginal and internal adaptation of five-unit implant-supported fixed partial dentures with different superstructure and abutment materials with two different implant systems. Materials and Methods: Two mandibular epoxy resin models (one for each implant system) were fabricated, and implants were inserted in the canine, first premolar, and first molar regions. Thirty impressions of each model were then made. The 30 models of each group were divided into three subgroups: group 1, titanium abutment with metal (nickel-chromium) framework; group 2, titanium abutment with zirconium framework; and group 3, zirconium abutment with zirconium framework. The replica technique was used to examine the marginal and internal gap values. For each restoration, 20 measurements were performed, and the data were evaluated statistically using analysis of variance and the least significant difference post hoc test. Results: The highest values for internal adaptation were observed at the occlusal surface in all groups. There were statistically significant differences in marginal measurements between subgroups. The smallest gaps were found in group 1 (79.361 mu m), and the largest gaps were found in group 3 (131.242 mu m). Conclusions: In this study, marginal and internal gap measurements were 79 to 131 mu m. The marginal discrepancy of the tested materials could be considered clinically acceptable.
Keywords: dental implants; marginal and internal adaptation; restorative materials; ONE-PIECE CASTINGS; DENTAL PROSTHESES; CERAMIC CROWNS; FIT; FRAMEWORKS; METAL; ACCURACY; ZIRCONIA; TITANIUM; COPINGS